Analisis Gaya Bahasa dalam Lirik Lagu ”Dimana Merdeka” Karya Kelompok Penerbang Roket - Arsalna Octo; Cantika Khairi Nissa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to analyze the language style used in the song lyrics as a tool to convey messages of social criticism. The problem that will be raised in this research is to deeply examine the song lyrics to find implied meanings that can enrich our understanding of the work. In addition, we will also examine how the use of words, metaphors and sentence structure in this song and how the social and political context when the song was created influenced the choice of language style used. The method used is descriptive analytic with literature study technique. The object studied is the lyrics of the song “Where is Freedom” by the Rocket Flyer Group. The results of the analysis show that the lyrics of this song have a very effective language style in conveying messages. The use of metaphors and everyday language makes it easy for song lyrics to be remembered by various groups. This research has the potential to be a reference for future research.